2012
DOI: 10.5489/cuaj.11276
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of pT0N0 at radical cystectomy: The Canadian Bladder Cancer Network experience

Abstract: Introduction: Radical cystectomy is the standard treatment for muscle invasive bladder cancer. We assessed clinical outcomes in patients found to have no evidence of disease (i.e., pT0N0) following radical cystectomy. Methods: We collected and pooled a database of 2287 patients who underwent radical cystectomy between 1993 and 2008 in eight centres across Canada. Of this number, 135 patients were found to have pT0N0 bladder cancer at the time of cystectomy. Survival data and prognostic variables were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…In a group of patients with CIS resistant to TURBT complemented with intravesical BCG therapy treated with RC, female sex was an independent risk factor for increased CSM (P=0.029) ( 50 ). Similar conclusions have been revealed in cohorts treated with RC, which had no evidence of disease (pT0N0) following RC ( 51 ). On the other hand the data published by Soave et al and Mitra et al showed no difference in survival among gender treated with RC for NMIBC ( 52 , 53 ).…”
Section: Discussionsupporting
confidence: 82%
“…In a group of patients with CIS resistant to TURBT complemented with intravesical BCG therapy treated with RC, female sex was an independent risk factor for increased CSM (P=0.029) ( 50 ). Similar conclusions have been revealed in cohorts treated with RC, which had no evidence of disease (pT0N0) following RC ( 51 ). On the other hand the data published by Soave et al and Mitra et al showed no difference in survival among gender treated with RC for NMIBC ( 52 , 53 ).…”
Section: Discussionsupporting
confidence: 82%